INVESTIGATING THE ROLE OF HAND PUPPETS IN REDUCING SPEAKING ANXIETY AMONG JUNIOR HIGH SCHOOL EFL STUDENTS - Muhammad Fikri Rivaldi; Yuri Lolita (Universitas Bina Bangsa Getsempena, 2026)
This study focuses on investigating the role of the hand puppet as a teaching medium in reducing speaking anxiety among junior high school EFL students through a qualitative study approach. The sample of this study was eight eighth-grade students from a junior high school in Surabaya who were purposively selected based on their experience of speaking anxiety in English classes. The students were involved in English speaking activities assisted by hand puppets during classroom instruction. Data were collected through semi-structured interviews and reflective journals to explore students’ perceptions and reflections on the use of hand puppets in English-speaking lessons. The collected data were analyzed using thematic analysis to identify recurring patterns and themes related to students’ emotional responses, confidence, and anxiety levels. The findings revealed that most students perceived hand puppets positively, as they helped create a more enjoyable and less intimidating learning environment. The use of hand puppets was found to reduce students’ fear of making mistakes, lower their anxiety, and enhance their confidence in speaking English. Although a small number of students expressed neutral or less positive responses due to personal preferences, the overall results indicate that hand puppets can function as an effective instructional medium to support students’ emotional comfort and engagement in speaking activities. Therefore, this study concludes that hand puppets have strong potential as an alternative teaching medium to reduce speaking anxiety and foster a supportive speaking environment for junior high school EFL learners.